Frauds and Errors Assessment During the Audit - Kanapickienė, Rasa; Gipienė, Gailutė; Jefimovas, Borisas (Ekonomika, 2004)
The work provides theoretical analysis of fraud and errors in financial reporting. The analysis of inherent risk investigates factors influencing the fraud and error risk. While assessing the inherent risk in documents reflecting business operation, the auditor has to choose the most effective way for collecting evidences proving that the accounting and financial reporting are free of material errors. The author offered a more specific classification of errors and suggests that all errors should be grouped as follows: 1) completeness, 2) existence, 3) errors in assessing powers and duties, 4) performance, 5) assessment, 6) measuring, 7) representing, and 8) revealing errors. While analysing the occurrence of fraud and errors resulting from the control system of the company, the investigations must cover the control environment, the accounting system, and the control procedures. The assessment of the control environment shall cover: 1) management philosophy and management style; 2) organisational structure of the company; 3) personnel policy. While analysing the error and fraud risk in the accounting system of a company, it is important to assess both individual accounting control procedures and the whole accounting system. When the analysis deals with the efficiency of the control procedures launched in the company, it has to assess 1) appropriate distinction of the staff jobs, 2) approval of the operations, 3) documentation, 4) relevant protection of the assets and entries, 5) control and assessment of business operations. The fraud and error risk depends on the auditor profile rather than on the company profile alone. The following features of an auditor are very important in detecting fraud and errors, namely: independency and professional scepticism. When there are circumstances indicating a probability of frauds and errors, the auditor shall consider their impact on the financial information and take up further procedures. The work provides an algorithm of the procedures designed by the authors.